The Role of Provider Characteristics in the Selection of Surgery or Radiation for Localized Prostate Cancer and Association With Quality of Care Indicators. (November 2018) - Satkunasivam, Raj; Lo, Mary; Stern, Mariana; Gill, Inderbir S.; Fleming, Steven; Wu, Xiao-Cheng; Anderson, Roger T.; Thompson, Trevor D.; Hamilton, Ann S.
Abstract : Introduction: We sought to identify the role of provider and facility characteristics in receipt of radical prostatectomy (RP) or external beam radiation therapy (EBRT) and adherence to quality of care measures in men with localized prostate cancer (PCa). Materials and Methods: Subjects included 2861 and 1630 men treated with RP or EBRT, respectively, for localized PCa whose records were reabstracted as part of the Centers for Disease Control and Prevention Breast and Prostate Patterns of Care Study. We utilized multivariable generalized estimating equation regression analysis to assess patient, clinical, and provider (year of graduation, urologist density) and facility (group vs. solo, academic/teaching status, for-profit status, distance to treatment facility) characteristics that predicted use of RP versus EBRT as well as quality of care outcomes. Results: Multivariable analysis revealed that group (vs. solo) practice was associated with a decreased risk of RP (odds ratio, 0.47; 95% confidence interval, 0.25-0.91). Among RP patients with low-risk disease, receipt of a bone scan that was not recommended was significantly predicted by race and insurance status. Surgical quality of care measures were associated with physician's year of graduation and receiving care at a teaching facility. Conclusions: In addition to demographic factors, we found that provider and facility characteristics were associated with treatment choice and specific quality of care measures. Long-term follow-up is required to determine whether quality of care indicators are related to PCa outcomes. Abstract : Supplemental Digital Content is available in the text.